The effectiveness of using non-traditional teaching methods to prepare student health care professionals for the delivery of mental state examination: a systematic review. (July 2015) - Xie, Huiting; Liu, Lei; Wang, Jia; Joon, Kum Eng; Parasuram, Rajni; Gunasekaran, Jamuna; Poh, Chee Lien
Executive summary : Background : With the evolution of education, there has been a shift from the use of traditional teaching methods, such as didactic or rote teaching, towards non‐traditional teaching methods, such as viewing of role plays, simulation, live interviews and the use of virtual environments. Mental state examination is an essential competency for all student healthcare professionals. If mental state examination is not taught in the most effective manner so learners can comprehend its concepts and interpret the findings correctly, it could lead to serious repercussions and subsequently impact on clinical care provided for patients with mental health conditions, such as incorrect assessment of suicidal ideation. However, the methods for teaching mental state examination vary widely between countries, academic institutions and clinical settings. Objectives : This systematic review aimed to identify and synthesize the best available evidence of effective teaching methods used to prepare student health care professionals for the delivery of mental state examination. Inclusion criteria : This review considered evidence from primary quantitative studies which address the effectiveness of a chosen method used for the teaching of mental state examination published in English, including studies that measure learner outcomes, i.e. improved knowledge and skills, self‐confidence and learners' satisfaction. Search strategy : A three‐step search strategy was undertaken in this review to search for articles published in English from the inception of the database to December 2014. An initial search of MEDLINE and CINAHL was undertaken to identify keywords. Secondly, the keywords identified were used to search electronic databases, namely, CINAHL, Medline, Cochrane Central Register of Controlled Trials, Ovid, PsycINFO and, ProQuest Dissertations & Theses. Thirdly, reference lists of the articles identified in the second stage were searched for other relevant studies. Methodological quality : Studies selected were assessed by two independent reviewers for methodological validity prior to inclusion in the review using the standardized critical appraisal instruments from the Joanna Briggs Institute's Meta‐Analysis of Statistics Assessment and Review Instrument (MASTARI) embedded within the System for the Unified Management, Assessment and Review of Information (JBI‐SUMARI). Any disagreements that arose between the reviewers were resolved through discussion between the reviewers. Data extraction : Data was extracted using data extraction tools developed by the Joanna Briggs Institute (JBI). Quantitative data was extracted from papers using standardized data extraction tools from the Joanna Briggs Institute's Meta‐Analysis of Statistics Assessment and Review Instrument (JBI‐MAStARI). Data synthesis : The included studies were found to be heterogeneous in terms of participants and teaching methods. Moreover, a wide variety of instruments were used to determine impact and outcomes of the teaching methods. Hence, findings of the included articles were presented in a narrative summary. Results : A total of 12 articles were included in this review with consensus from all reviewers. The evidence retrieved in this study suggests that non‐traditional teaching methods, such as videotapes, virtual simulation, standardized patients and reflection, improve learners' understanding and skills of mental state examination as opposed to traditional teaching methods like lectures and provision of reading materials. However, studies that specifically compared the effectiveness of one method over another were limited to comparison between lectures with videotaped interviews and virtual simulations. It was shown that both videotaped interviews and virtual simulations were superior to lectures. In videotaped teaching, interactions between patients and learners performing mental state examination were shown for the learner's discussion while virtual simulations mimicked patient symptoms in computer applications. Virtual simulation was notably a unique learning opportunity for the learners as it allowed learning to take place without the use of diminishing real life resources. However, in view of the high cost and learners' difficulty in negotiating the virtual environment, videotaped teaching remained as the more commonly used method of teaching mental state examination. Conclusions : This systematic review study identified teaching strategies utilized in the teaching of mental state examination and their effectiveness. Videotapes was the most widely used and effective approach, that is, until the issue of high cost and ease of maneuver in virtual simulation could be overcome. There were also potential benefits of other teaching, such as reflection and use of standardized patients, and educators could consider these in the teaching of mental state examination. Future research could focus more on the comparison of various teaching methods to offer more evidence on the use of one teaching method over another. Implications for educational practice : Educational practitioners could consider the evidence when deciding about utilization of different methods of teaching mental state examination. Implications for research : Future research could further inform the effectiveness of various teaching methods using randomized controlled trials and examine the impact of innovative teaching methods such as gamification that has rarely been utilized in the teaching of mental state examination.